Sarcasm as Impoliteness Device in Indonesian and American Context (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
This paper discusses the differences between the Indonesian version of sarcasm and the American version based on the definitions provided by the dictionaries. The next part of this paper describes the point where the colloquial use of sarcasm in Indonesian and American English also differs. The Indonesian version of sarcasm loses the satirical, ironic, and humorous elements of American sarcasm. The last part of this paper presents a theoretical comparison of the two versions of sarcasm. Indonesian sarcasm falls into the categories of positive impoliteness and negative impoliteness. On the other hand, American sarcasm is a mock politeness or off-record impoliteness according to Culpeper. Bilingual speakers of English and Indonesian should be cautious of this phenomenon to avoid potential communication disasters. The main limitation of this paper is that the data presented in this paper are far from comprehensive.